2005
DOI: 10.1007/s10350-005-0156-z
|View full text |Cite
|
Sign up to set email alerts
|

The Location and Contents of the Lateral Ligaments of the Rectum: A Study in Human Soft Cadavers

Abstract: The lateral ligaments of the rectum were located at posterolateral side of the rectum. They were closer to the coccyx than to the sacral promontory. Its component was loose connective tissue containing multiple small nerves. There was no artery found in any lateral ligaments by histologic study. Small arterioles and venules were detected 11 percent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The presence of lateral ligaments has been debated in previous anatomical studies [36-39]. Pak-art et al [37] beautifully demonstrated an actual lateral ligament by using a cadaveric hemipelvis dissection and concluded that the lateral ligament was present and that it consisted of loose connective tissue with clusters of small nerves. However, according to other observers, the actual position of the lateral ligament was different.…”
Section: Potential Benefits Of Robotsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of lateral ligaments has been debated in previous anatomical studies [36-39]. Pak-art et al [37] beautifully demonstrated an actual lateral ligament by using a cadaveric hemipelvis dissection and concluded that the lateral ligament was present and that it consisted of loose connective tissue with clusters of small nerves. However, according to other observers, the actual position of the lateral ligament was different.…”
Section: Potential Benefits Of Robotsmentioning
confidence: 99%
“…However, according to other observers, the actual position of the lateral ligament was different. Kinugasa et al [39] insisted that it was located between the mesorectum and the pelvic wall at the ventrolateral side of the pelvic splanchnic nerves; however, Pak-art et al [37] observed that it was located at the medial side of the pelvic splanchnic nerves originating from the anterior foramina of S3 and S4. Based on our perspectives, definite ligamentous structures between the rectal wall and the pelvic wall are present, and these structures are usually located at an adjacent structure, such as the pelvic plexus or the middle rectal artery.…”
Section: Potential Benefits Of Robotsmentioning
confidence: 99%
“…However, Sato et al reported that the middle rectal artery was observed in only 22% of cases (35). Pak-art et al reported that no artery was found histologically in any lateral ligament (36). Moreover, studies on the lymphatic flow of the lateral ligament were mainly based on the macroscopic anatomy and on speculations from the clinical metastatic features (1,31).…”
Section: Fascial Structures and Lymphatic Distributionsmentioning
confidence: 99%
“…As for their placement, 17 were located laterally in the rectum, 10 posteriorly and 3 posterolaterally, while their number ranged from 1-5 [39]. However, other research teams managed to find a neurovascular component in [40,41] or above them [42]. Nonetheless, because of the general effort to improve survival rates for patients with rectal cancer (especially those located in the lower rectum), there is a resurgence of research into these ligaments.…”
Section: Mesorectum and Surrounding Fasciasmentioning
confidence: 99%